Medico-social substantiation of the issue of quality of life in patients with breast cancer and finding ways to improve it - Zub, V.О. (Medicni Perspektivi, 2023)
The quality of life of patients is one of the indicators of the medical care effectiveness for cancer patients. In order to study the main aspects of the quality of life of patients with breast cancer, a survey of 400 patients at the stage of their inpatient treatment in oncological institutions in nine regions of Ukraine (Chernihiv, Zaporizhia, Dnipropetrovsk, Kyiv, Poltava, Khmelnytsky, Ivano-Frankivsk, Zakarpattia and Lviv) using the EORTC QLQ-C30 and EORTC QLQ-BR45 questionnaires was carried out. In Ukraine, as of the pre-war period (November 2021 – February 2022), the quality of life of breast cancer patients equaled 53.22 on a 100-point scale. The most pronounced impact of breast cancer on the quality of life of the patient was observed in the psycho-emotional sphere (71.26), role functioning (70.48), views on future prospects (30.95). Patients complained of financial difficulties (44.19), fatigue (35.16), sleep disturbances (33.00), hair loss (43.41), as well as decreased sexual function (16.06) and pleasure (18.16 points). Given the low quality of life of breast cancer patients, they need psychological support, which should be aimed at adapting to the manifestations of the disease and future prospects, and the quality of life of patients should be one of the indicators in the course of treatment and providing psychological support. Since patients who have received social and psychological support from their doctors and friends/family have higher quality of life, we consider it necessary to focus on developing a comprehensive program to support breast cancer patients in collaboration with society, family and workplace.